Eksistensi Manusia Dalam Pancasila Perspektif Jean-Paul Sartre - Sultan Maulana, Dimas Rangga (Pancasila and Civics Education Journal (PCEJ), 2024)
This article discusses human existence in Pancasila. The discussion will focus mainly on the second principle which reads